A proposed resistance-to-time converter with switching impulse calibrators for application in resistive bridge sensors - Mohammad, Zahangir Alam; Khan, Sheroz; Adam, Ismail; Abdul Kadir, Kushsairy; Nordin, Anis Nurashikin; Ibrahim, Siti Noorjannah (Institute of Advanced Engineering and Science (IAES), 2018)
This paper presents a simple resistance-to-time converter. It consists of two voltage comparators, a ramp voltage generator, two logic gates and impulse voltage calibrators. A square-wave generator circuit is suggested in this paper. The design is simple and independent of the OPAMP offset issues. The resulting square-wave is rectified to get its DC equivalent and to a triangular output; the two outputs are applied to a comparator for generating a digital output with a duty cycle proportional to a change in resistance upon which is dependent the DC.